Analysis of investment attractiveness redevelopment projects the industrial areas in Kiev - Yevsyukov, T.; Tsvyakh, O.; Openko І. (Land Management, Cadastre and Land Monitoring, 2017)
At the present stage of development of land relations in major cities of our country important issue is the development of investment, attract and use foreign investment. According to the Law of Ukraine "On investment activity" under the investment necessary to understand "all types of property and intellectual values invested in business and other activities, which resulted in creating profit (income) or social effect is achieved." For the economy of any city, including the city. Kyiv and development of urban land use, renovation of industrial areas deindustrialization of inefficient production centers, it is extremely important investment activity (foreign investment) as one of the most effective mechanisms for the development and activities of national companies. The purpose of the article to analyze the investment attractiveness of the redevelopment projects of industrial areas to economic development of eco-industrial land use in Kiev, despite the downward trend in investment activity of domestic enterprises, the need for technical and technological modernization of production as well as the entire market infrastructure, redevelopment of industrial areas. Redevelopment areas – this is a comprehensive activity aimed at changing the existing construction work carried out with the help of large investments (investments) in reconstruction; renovation of; overhaul; demolition; conversion; improving the environment, which results in a positive effect on economic, social and environmental aspects. Investment and construction projects related to redevelopment of industrial land use (objects) in the management of the city, characterized by considerable risks given the high capital intensity, binding to a specific area, and the impact of other internal and external factors. That is why this investment activity should be ensured exceptional dynamic management to ensure the quality of implementation and the necessary level of profitability and sustainability of urban areas. Thus, the development of industrial zones in the city through redevelopment can be valuable not only from the standpoint of economic development of the territory, but also provided the interconnected nature of urban problems, employment, population, environment and related changes in the social sphere and the administrative and legal system big cities. In any case, the main, ultimately, the effectiveness of investments factor is the economic efficiency of the project of de-industrialization. Today the economic evaluation of the effectiveness of investment and construction projects related to the redevelopment of industrial areas carried out in several ways, one of which involves the use of discounted costs of development project. Summarizing the foregoing, we note that the key advantage of typical projects of redevelopment of industrial areas in Kiev are: the uniqueness of the territory (comparatively extensive area not far from downtown, provision of energy facilities, proximity to important waterway in Kyiv); active participation of local authorities (commitment to the development of transport and social infrastructure, landscaping); balance of residential areas and workplaces (project planning developed under ecological and economic aspects of the functional use of land). However, the main disadvantages should include: significant capital investments, low returns such projects redevelopment of industrial areas (discount rate redevelopment project for the industrial area, according to our estimates of 41.9%). Key words: investments, investment activity, redevelopment, industrial area, land use.